PENELITIAN PENDAHULUAN SEBARAN UKURAN DAN REPRODUKSI IKAN BOTIA (Botia macracanthus) DI PERAIRAN DAS MUSI (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2026)
Study on reproduction and spawning of Botia (Botia macracanthus) was conducted at the upper and middle part of Musi river basins, since April 1997 to March 1998. Study was carried out by survey method, with sampling site were selected based on purposived method and the result of the previous study. The sampling site for Botia fry was at Danau Cala while for brood stock was at Muara Lakitan. Sampling was conducted in April, June, August, October, December and February. The result showed that the somatic index maturity start in June (TKG I), August (TKG II), and October (TKG III). Botia spawning three times a year with spawning season starting from December to February.Keywords : Musi river basins, spawning, botia